Klar Framgang! 2017
DOI: 10.18261/9788215030258-2017-4
|View full text |Cite
|
Sign up to set email alerts
|

3 Norske resultater fra ePIRLS – Online Informational Reading

Abstract: HILDEGUNN STØLE OG KNUT SCHWIPPERTSAMMENDRAG I denne artikkelen presenteres den nye elektroniske leseprøven ePIRLS. Norske resultater analyseres i lys av bakgrunnsvariabler som elevenes kjønn, digitale aktiviteter og fritidslesing. Et par av disse sammenliknes med elevresultatene fra den tradisjonelle, papirbaserte PIRLS. I tillegg sammenliknes norske 5.-trinnselevers resultater med noen av de andre landenes resultater, i hovedsak våre naboland Danmark og Sverige. NØKKELORD ePIRLS | online informasjonslesing |… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Adolescents who reported reading fiction performed significantly better on PISA 2009 than those who read other kinds of reading material (magazines, non-fiction, fiction, newspapers and comics) (Jerrim & Moss, 2019). Norwegian children who enjoyed reading and read in their spare time, performed better than those who did not, both on the paper-based PIRLS 2016, as well as on the online informational reading assessment (ePIRLS) in 2016 (Støle & Schwippert, 2017). Mol and Jolles (2014) found that students' enjoyment of reading was socially stratified and related to gender.…”
Section: Parental Readingmentioning
confidence: 99%
“…Adolescents who reported reading fiction performed significantly better on PISA 2009 than those who read other kinds of reading material (magazines, non-fiction, fiction, newspapers and comics) (Jerrim & Moss, 2019). Norwegian children who enjoyed reading and read in their spare time, performed better than those who did not, both on the paper-based PIRLS 2016, as well as on the online informational reading assessment (ePIRLS) in 2016 (Støle & Schwippert, 2017). Mol and Jolles (2014) found that students' enjoyment of reading was socially stratified and related to gender.…”
Section: Parental Readingmentioning
confidence: 99%
“…Las consideraciones sobre una generación que pueda desarrollar aptitudes solo por estar inmersos en un entorno tecnológico han sido subsanadas por investigaciones más precisas y matizadas (Prensky, 2011;Rowlands et al, 2008), pero, en la práctica, pareciera que aún se cree que los niños pueden desenvolverse solos en el ecosistema digital por el mero hecho de nacer en un ambiente con pantallas. Si bien existen discusiones sobre el desarrollo de la lectura comprensiva en diferentes formatos (papel o digital), en países pioneros en tecnología como Noruega (Støle y Schwippert, 2017;Støle, 2020) se considera que para arribar a la alfabetización plena se requiere la incorporación de ficciones digitales sin perder de vista su impronta estética, en niveles equilibrados con la lectura en papel: una convivencia entre mundos, en diálogo unos con otros (Ramada-Prieto, et al, 2021;Ramada Prieto y Turrión Penelas, 2019). La idea de que la lectura digital se asemeja a una conversación (Gaudric, Mauger y Zunigo 2016, p. 11) abona la noción de una ampliación de la comprensión dialógica, siendo, por tanto, fácilmente articulable con los universos educativos preexistentes.…”
Section: Hibridez Del Contexto Culturalunclassified